Peripartum outcomes in a large population of women with pulmonary arterial hypertension associated with congenital heart disease. (July 2019) - Li, Qiangqiang; Dimopoulos, Konstantinos; Liu, Tianyang; Xu, Zhuoyuan; Liu, Qian; Li, Yanna; Zhang, Jun; Gu, Hong
Aims: Pulmonary arterial hypertension is a severe complication in patients with congenital heart disease and poses a significant risk to women wishing to become pregnant. This study describes the clinical presentation, maternal outcomes and risk factors for the peripartum period in women with pulmonary arterial hypertension related to congenital heart disease (PAH-CHD). Methods: All pregnant women with PAH-CHD who were admitted for delivery in a tertiary center between February 2011–September 2016 were included. Logistic regression analysis was used to identify predictors of the combined endpoint of maternal death, severe heart failure requiring treatment, or pulmonary hypertensive crisis. Results: Ninety-three women (94 pregnancies) were included. Average age was 27.5 ± 4.4 years. Thirty (31.9%) patients had Eisenmenger syndrome, 51 (54.3%) had pulmonary arterial hypertension associated with systemic-to-pulmonary shunts, and 13 (13.8%) had pulmonary arterial hypertension with corrected congenital heart disease. Twenty-three (24.5%) women required admission for delivery within two days from presentation. Elective Cesarean section was performed in 95.7% of women, with intravertebral anesthesia in 93.6%. Fifty-one (54.2%) patients received pulmonary arterial hypertension therapies during pregnancy. Six (6.4%) women died, 33 (35.1%) developed heart failure and 10 (10.6%) had a pulmonary hypertensive crisis. Patients who met the combined endpoint ( n = 34, 36.2%) were more likely to have Eisenmenger syndrome or repaired defects ( p < 0.001). Other risk factors in the multivariate model included lower arterial blood oxygen saturation, higher brain natriuretic peptide, and pericardial effusion on echocardiography. Conclusion: Maternal mortality and morbidity remain high in PAH-CHD patients, who should be counseled on the risks of pregnancy and managed in a tertiary multidisciplinary environment to improve prognosis.